Geopolitical Risk and Investor Reaction in Indonesia: Evidence from Russia-Ukraine’s Conflict - Wiku Suryomurti (Universitas Darussalam Gontor, 2023)
This study investigates the impact of Russia-Ukraine’s conflict on stock market performance in emerging countries, specifically the stock market in Indonesia. We use event study to examine the market reaction towards the conflict and the military action of Russia. The market react negatively after the military action by Russia on 24 February 2022. Overall, the result suggest that the Indonesia stock market respond immediately to the political conflict between Russia and Ukraine. Furthermore, the scale of the reaction varies across different stocks and industries. The policy makers need to implement strategic action to mitigate the political risk of the on-going conflict. This study is one of the first study to do in-depth investigation of potential impact of Russia-Ukraine conflict on Indonesia Stock market.